FACTORS OF CREATING A NATIONAL MODEL OF HOUSING POLICY IN UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2023)
The fundamental reforms implemented in Uzbekistan in recent years are creating a basis for the development of the country's socio-economic and cultural life. In this process, special emphasis is placed on providing the population with quality and affordable housing that meets local requirements, state support for the housing sector, creating conditions for enterprises specializing in the production of building materials and state support attention is being paid . In particular, as a result of increased attention to housing policy in recent years, the scale of housing construction in cities and villages has expanded. These circumstances help to meet the demand of the population for housing. However, conducting the housing policy based on the national model is becoming an urgent task. This article analyzes the conditions for creating a national model of housing policy.